THE IMPACT OF SLEEP DEPRIVATION ON THE DEVELOPMENT OF OBESITY: A REVIEW OF THE LATEST RESEARCH - Szerenos, Nicol; Trocka, Daria; Woroniecka, Natalia; Stadnik, Luiza; Przybysz, Karolina; Kozłowska, Alicja; Dzwonkowski, Jakub; Dzwonkowska, Adela; Rachoń, Jarosław; Zienkiewicz, Natalia (International Journal of Innovative Technologies in Social Science, 2026)
Objective: The aim of this study is to analyze the current state of knowledge regarding the relationship between sleep deprivation and the risk of obesity progression, with particular emphasis on the underlying pathophysiological mechanisms and the therapeutic potential of interventions aimed at optimizing both the quality and duration of sleep.Materials and Methods: This review is based on an analysis of contemporary medical literature, including epidemiological data, meta-analyses of prospective cohort studies, and findings from experimental and clinical intervention studies published up to 2026.Results: The available body of evidence indicates a significant, non-linear J-shaped relationship between sleep duration and body mass index (BMI). Sleep lasting 7–8 hours per night is considered optimal for protection against excessive weight gain, whereas shorter sleep duration is associated with up to a 55% increase in the risk of obesity. The key mechanisms underlying this association include hormonal dysregulation within the ghrelin–leptin axis, characterized by elevated levels of the orexigenic hormone ghrelin and reduced levels of the satiety hormone leptin, resulting in direct stimulation of hunger centers. This phenomenon is accompanied by disturbances in energy homeostasis, manifested by an increase in daily energy intake of approximately 250–300 kcal without a corresponding compensatory increase in energy expenditure. At the metabolic level, reduced insulin sensitivity of peripheral tissues and a tendency toward preferential accumulation of intra-abdominal adipose tissue have been observed, promoting the development of visceral obesity. These processes are further amplified by neurobiological mechanisms, including heightened responsiveness of the brain’s reward system to highly caloric food stimuli, leading to impaired control over energy intake. Furthermore, evidence from intervention studies suggests that extending sleep duration in overweight individuals may result in a statistically significant reduction in spontaneous caloric consumption, averaging approximately 270 kcal per day.Conclusions: Sleep deprivation represents a significant, modifiable, and independent risk factor for obesity and its associated cardiometabolic disorders. In light of the available scientific evidence, routine assessment of sleep duration and quality should be incorporated into obesity diagnostic protocols. Sleep hygiene should be recognized as a third fundamental pillar of obesity prevention and treatment strategies, alongside dietary therapy and physical activity.